Transparent polycrystalline γ-AlON fabricated using a hybrid sintering process. (15th March 2021) - Tsabit, Ayman Muhammad; Yoon, Dang-Hyok
Abstract: This paper reports the properties of polycrystalline transparent γ-AlON fabricated using a hybrid sintering process of hot pressing and pressureless sintering. The overall aim was to reduce the time taken for the two-step pressureless sintering process. Using Al2 O3 and AlN as starting materials with 0.1 wt. % Pr2 O3 added as a sintering additive, hot pressing was performed at 1500°C under 20 MPa for 1, 2, and 3 hr followed by pressureless sintering at 1940°C for 10 hr in an N2 atmosphere. The effects of the hot pressing time and Pr2 O3 addition on the phase evolution, microstructure, mechanical properties, and optical transmittance of γ-AlON were examined. The γ-AlON fabricated using a hybrid process showed ≧ 80% transmittance, highlighting the feasibility of this process. Graphical abstract: Image, graphical abstract